Determinants of changes in electricity generation intensity among different power sectors. (July 2019) - Cheng, Shulei; Wu, Yinyin; Chen, Hua; Chen, Jiandong; Song, Malin; Hou, Wenxuan
Abstract: This study analyzes the determinants of changes in electricity generation intensity in China and further uncovers the reasons for the differences between the changes in electricity generation intensity in the thermal and sustainable power sectors. By developing a factorial-intertemporal nested decomposition technique using the refined Laspeyres index, we demonstrate the contributions of electricity generation structure, electricity generation-to-consumption ratio, production electricity consumption intensity, residential electricity consumption intensity, and electricity consumption loss intensity effects. Although the electricity generation intensity of the thermal power sector has been lower than that of the sustainable power sector, the latter has declined remarkably and has remained the key sector driving the overall changes in electricity generation intensity. Meanwhile, the effect of electricity consumption intensity is the main factor that reduces electricity generation intensity. Moreover, the impact of production electricity consumption intensity in the thermal power sector exceeds its impact in the sustainable power sector. Ultimately, we find that the differences between the changes in electricity generation intensity in the thermal and sustainable power sectors are mainly due to their differences in production electricity consumption intensity. Highlights: Changes in electricity generation intensity are attributed to five effects. Generation intensity differences between the thermal and sustainable power sectors are analyzed. Power generation and electricity consumption are linked. A factorial-intertemporal nested decomposition technique of the Refined Laspeyres index is developed. Electricity consumption intensity effect contributes more than other effects.